THE ROLE OF DESIGN THINKING IN ARTIFICIAL INTELLIGENCE DISRUPTION: A SYSTEMATIC LITERATURE REVIEW - Havidotinnisa, Siti; Afini , Firli; Saryadi , Yadi; Mufti , Imas (Multifinance, 2024)
This research aims to explore the role of Artificial Intelligence (AI) and Design Thinking in supporting digital transformation in various sectors, with a focus on innovation, sustainability, and operational efficiency. The study also seeks to analyze the relevance of both approaches in business and academic contexts, particularly in creating creative and human-centered solutions in the era of technological disruption. To achieve these objectives, this study used a systematic literature review method, by analyzing ten accredited and indexed articles in reputable international journals. The results showed that AI acts as a disruptive technology that not only improves efficiency but also accelerates digital transformation. Studies such as the one by Di Vaio et al. (2020), which received 1015 citations, highlighted how AI supports the development of sustainable business models. Additionally, research by Verganti et al. (2020) identified that Design Thinking remains relevant as an adaptive innovation approach, especially in the face of challenges posed by AI. The integration between AI and Design Thinking is also reflected in the study of Pham et al. (2022), which shows how creative approaches can maximize the potential of advanced technologies such as big data. Overall, this study confirms that the combination of AI and Design Thinking offers a comprehensive solution to deal with the complexities of digital transformation across various sectors.